2020
DOI: 10.1007/s00330-020-06672-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrating artificial intelligence into the clinical practice of radiology: challenges and recommendations

Abstract: Artificial intelligence (AI) has the potential to significantly disrupt the way radiology will be practiced in the near future, but several issues need to be resolved before AI can be widely implemented in daily practice. These include the role of the different stakeholders in the development of AI for imaging, the ethical development and use of AI in healthcare, the appropriate validation of each developed AI algorithm, the development of effective data sharing mechanisms, regulatory hurdles for the clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(91 citation statements)
references
References 35 publications
0
88
0
3
Order By: Relevance
“…Another implementation challenge we found, the role of evidence on innovation implementation, has been discussed extensively in the field of evidence-based healthcare [41]. Scientific evidence is an important determinant of innovation implementation for practitioners, a finding that also appears to hold for AI in radiology [8,21,41,42]. It thus follows that AI applications for radiology reflect a trend in the field of medical imaging to engage with technologies that have yet to prove their promises of contributing to the improvement of the quality or efficiency of healthcare [43].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Another implementation challenge we found, the role of evidence on innovation implementation, has been discussed extensively in the field of evidence-based healthcare [41]. Scientific evidence is an important determinant of innovation implementation for practitioners, a finding that also appears to hold for AI in radiology [8,21,41,42]. It thus follows that AI applications for radiology reflect a trend in the field of medical imaging to engage with technologies that have yet to prove their promises of contributing to the improvement of the quality or efficiency of healthcare [43].…”
Section: Discussionmentioning
confidence: 66%
“…The interviews showed that computer science and programming knowledge required in the development of AI algorithms are not present-day competencies of radiologists. However, some technical understanding is imperative for quality and safety assessment and therefore create trust in the AI application's reliability [8,21,30].…”
Section: Identified Facilitating Factors For Ai Implementation In Radmentioning
confidence: 99%
See 1 more Smart Citation
“…For radiologists, it is crucial to know the strength and weaknesses of the technology that they use to improve quality, ensure safety and understand artefacts [19,20]. Additionally, radiologists need to understand technical information about the applications [21] to recognize the strengths and pitfalls of AI applications [22]. Information about the training data of algorithms and whether external validation was performed helps radiologists assess the credibility and applicability of an AI application in their hospital [23].…”
Section: Technical Characteristicsmentioning
confidence: 99%
“…2. Technical validation: once the algorithm has been trained, it is difficult to prove its robustness and reliability as it works like a black box [3]. 3.…”
mentioning
confidence: 99%